The more concentrated, the better represented? The geographical concentration of immigrants and their descriptive representation in the German mixed-member system - Lucas Geese; Diana Schacht (International Political Science Review, 2019)
Does the geographical concentration of ethnic minorities influence their descriptive representation in closed-list systems? Counterintuitive to the idea that single-member district electoral rules are necessary for minorities' geographical representation, we argue that, in closed-list systems, parties are incentivised to allocate promising list positions to those minority candidates who are based in geographical areas where minorities concentrate. Empirically, we provide a case study of the list positions of dual candidates of immigrant origin running in the German mixed-member system in 2013. Results show a relationship between the list positions of candidates of immigrant origin and geographical concentrations of immigrant-origin residents.
Keywords: 330; descriptive representation; mixed-member systems; immigrant-origin candidates; geographical concentrations; ethnic minorities; closed-list systems